The fuzzy multi-objective distribution planner for a green meat supply chain - Mohammed, Ahmed; Wang, Qian (International journal of production economics, 2017)
It is often a complex task for developing a product distribution plan of a supply chain (SC) network and a supportive decision tool can be useful for easing the role of decision-making. On the other hand, it has been increasingly becoming a demand to design a supply chain network considering the environmental impact as a new dimension as required by authorities in many countries. This paper describes a development of a product distribution planner for a three-echelon green meat supply chain (MSC) design in terms of issues including numbers and locations of facilities that should be opened in association with the product quantity flows. These issues were formulated into a fuzzy multi-objective programming model (FMOPM) with an aim to minimize the total cost of transportation and implementation, the amount of CO2 emissions in transportation and the distribution time of products from farms to abattoirs and from abattoirs to retailers, and maximize the average delivery rate in satisfying product quantity as requested by abattoirs and retailers. To optimize the four objectives simultaneously, three solution methods were investigated and used; which are the LP-metrics method, the ε-constraint method and the goal programming method. The best solution was determined using the Max-Min method by comparing the obtained Pareto solutions. A case study was examined based on the developed model that demonstrates its applicability in making an optimal product distribution plan in trade-offs among the four objectives.